Legal Counseling as an Effort to Prevent Human Trafficking against Children in the Digital Era at SMAN 3 OKU - Banjarani, Desia Rakhma (Faculty of Law, Universitas Sultan Ageng Tirtayasa, 2025)
Nowadays, Indonesia is still used as a field for human trafficking crimes, especially most of the victims are underage teenagers or child. The factors that cause human trafficking in Indonesia are poverty, low education, and changes in world globalization. Thus, based on this, legal counseling is needed as a form of prevention of human trafficking crimes against children in the digital realm. In this regard, the formulation of the problem in this community service activity is: How do the counseling participants respond and do the legal counseling participants understand the mode of human trafficking crimes in the digital realm?. The results of the counseling showed that the response of the counseling participants to the activities was very good. This can be seen from the enthusiasm of the students of SMA Negeri 3 Ogan Komering Ulu in participating in interactive discussions both by asking and answering questions about the counseling theme. During the counseling activities, it was not only carried out one way, the students of SMA Negeri 3 Ogan Komering Ulu played a very active role in asking questions so that the expected discussion could be carried out well. The legal counseling participants already understand the mode of human trafficking in the digital realm. This can be seen during the question and answer process and quizzes where most students understand the material related to human trafficking. The quiz was carried out through the Kahoot! application.